2017
DOI: 10.1007/s00228-017-2393-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cytochrome P450 2C19 polymorphism on adverse cardiovascular events after drug-eluting stent implantation in a large Hakka population with acute coronary syndrome receiving clopidogrel in southern China

Abstract: Our results shed new light on the important benefit of testing CYP2C19 polymorphisms before prescribing clopidogrel in patients treated with drug-eluting stent implantation after PCI. The testing may help to optimize pharmacotherapy effectiveness by providing individualized treatment to the Chinese population. Our findings mandate further studies aimed at initiating genome-based personalized antiplatelet therapy in a Hakka population in southern China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
1
7
0
3
Order By: Relevance
“…Many studies have proved that the CYP2C19*2 LOF alleles (*1/*2, *2/*2) increase the risk of MACE [33,34]. Our study also showed that intermediated metabolizer [35]. such variation may include genetic, non-genetic, and physiologic agents among the patients.…”
Section: Discussionsupporting
confidence: 61%
“…Many studies have proved that the CYP2C19*2 LOF alleles (*1/*2, *2/*2) increase the risk of MACE [33,34]. Our study also showed that intermediated metabolizer [35]. such variation may include genetic, non-genetic, and physiologic agents among the patients.…”
Section: Discussionsupporting
confidence: 61%
“…There was also Personalized antiplatelet therapies based on platelet function assays have failed to demonstrate any significant clinical benefit in previous clinical trials [16][17][18][19] . The great variability of the platelet function tests (PFTs) is a major limitation in using such assays to assess the pharmacodynamic efficacy of antiplatelet therapy 20,21 Previous studies have suggested there might be clinical benefits of genotype-guided therapy in reducing bleeding and ischemic complications for patients undergoing stent implantation [23][24][25][26][27][28][29]…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested there might be clinical benefits of genotype‐guided therapy in reducing bleeding and ischemic complications for patients undergoing stent implantation. An analysis of the CHARISMA (Clopidogrel for High Atherothrombotic Risk and Ischemic Stabilization, Management, and Avoidance) trial showed bleeding events were significantly reduced in clopidogrel‐treated patients who are carriers of CYP2C19 LOF alleles.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of clinical trials have observed that CYP450 genetic polymorphisms, especially the CYP2C19 loss-of-function ( CYP2C19 * 2 and CYP2C19 * 3 ) and/or gain-of-function ( CYP2C19 * 17 ) variants, can affect the antiplatelet efficacy of clopidogrel and the clinical outcomes (Chen et al, 2008a ; Paré et al, 2010 ; Zhang et al, 2015b , 2017 ; Sun et al, 2016 ). Evidences showed that the CYP2C19 intermediate metabolizers (IM, genotyped as CYP2C19 * 1 * 2 or CYP2C19 * 1/ * 3 ) and CYP2C19 poor metabolizers (PM, genotyped as CYP2C19 * 2/ * 2, CYP2C19 * 2/ * 3 , or CYP2C19 * 3 * 3 ) showed obviously increased risk of recurrence of ischemic events than CYP2C19 extensive metabolizers (EM, genotyped as CYP2C19 * 1 * 1 ) after PCI (Mega et al, 2010 ; Mao et al, 2013 ; Zhong et al, 2018 ). However, only 12% of individual variability of clopidogrel response can be explained by the CYP2C19 LOF allele, age, body mass index (BMI), and other clinical factors also contribute to this variability (Bonello et al, 2010 ; Jiang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%